Pengamanan Perintah Koneksi ke Database MySQL Menggunakan Algoritma Caesar Cipher dan Algoritma Stout Codes - Surya Darma Nasution (Bulletin of Information Technology (BIT), 2024)
The MySQL database system is one of the database systems that is widely used in the world, both for personal and corporate purposes. However, the increasing number of cyber attacks occurring on database systems makes it increasingly important to secure data security in database systems. Cyber attacks can be via SQL Injection or hacking via connection commands to the database using the application whose database you want to hack. This is the focus of the problem, so it is necessary to secure connections to the database using cryptographic algorithms. This research aims to improve the security of the MySQL database system by implementing the Caesar Cipher cryptography technique and the Stout Codes compression technique in connection commands to the database via a client application built using the Visual Basic programming language. The testing method used in this research is experimental, where the MySQL database system is tested using ordinary connection commands and connection commands that have been encrypted with the Caesar Cipher algorithm and the Stout Sodes algorithm. The test results show that the use of the Caesar Cipher and Stout Codes crypto-compression systems can increase the security of the MySQL database system by making access difficult for unauthorized parties with a success percentage of 100%. Thus, it is hoped that this research can contribute to improving the security of the MySQL database system which is currently increasingly vulnerable to cyber attacks